KANTONG SEMEN DAN PLASTIK SEBAGAI PRODUK KREATIF DI DESA BUGEL, KECAMATAN SEKARAN, KABUPATEN LAMONGAN MELALUI PROGRAM ISUK (INVESTASI SAMPAH UNTUK KESEHATAN) - Ikhsan, Nur; Fitrahayunitisna, Fitrahayunitisna; Marcella, Marcella; Hosensyah, Nadya Pradita (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2022)
The partnership between Sekaran Community Health Center and Tyaga Art Management in the PTMA (Integrated Non-Communicable Disease Management) program is a collaboration to create an innovative health program called ISUK (Investment in Waste for Health). Through the ISUK program, it was identified that there is a large amount of cement bag and plastic waste that can be used as raw materials for creative industries to increase economic value and self-reliance. Therefore, training is needed to utilize cement bags and plastic into creative products with economic value that can compete in the market. The method of this activity involves training conducted in collaboration with the Sekaran Health Center. The results of the creative products include bags, tote bags, and wallets. The community has shown high enthusiasm for participating in this activity, with some even planning to pursue it as a self-sustaining business.